The local and the universal in Ecuadorian art applied to architectural education - Benavides-Alvarez, Javier; Revelo-Morales, Nataly (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
The relationship between the local and the universal in creative processes is examined, using the methodology of Architectural and Urban Design I Workshop from the Architecture program at Pontificia Universidad Católica del Ecuador (PUCE) during 2022. The study analyzes how students can integrate local traditions with universal principles through mimesis and abstraction, referencing two comparative cases: one Ecuadorian and one international. The methodology aims to ¨ not only theoretically, but also through a practical process that transforms real objects into abstract forms. This approach facilitates the understanding of universal patterns present in various cultural and artistic expressions, allowing their adaptation to the architectural context.